'Watch and wait' after chemoradiotherapy for rectal cancer. Issue 9 (25th July 2018) - Mullaney, Tamara G.; Lightner, Amy L.; Johnston, Michael; Keck, James; Wattchow, David
Abstract : Surgery remains the cornerstone of rectal cancer treatment. However, there is significant morbidity and mortality associated with pelvic surgery, and the past decade has illustrated that a cohort of rectal cancer patients sustain a remission of local disease with chemoradiation alone. Thus, questions remain regarding the optimal management for rectal cancer; namely, accurately identifying patients who have a complete pathologic response and determining the oncologic safety of the observational approach for this patient group. This review aims to summarize the current evidence to provide an overview to the 'watch and wait' approach in rectal cancer patients with a complete response to neoadjuvant chemoradiation therapy.